PERANCANGAN SISTEM INFORMASI AKUNTANSI MASJID - ISWANDI, ISWANDI (Sainstek : Jurnal Sains dan Teknologi, 2011)
The objective of the research is to describe the mosque committee preparation in arranging the description of loan mosque of orphan and MDA per month. This research is a descriptive reasearch.  In collecting the data, the data will be collected through observation and interview. Those data will be analyzed and interpreted in form of table. If it is possible, the data will be corralted among the variables. Finding of the research is hoped that they can give smart solution for the next researcher to do the further research.Key words: information system, accountancy of masjid